2017
DOI: 10.1038/s41598-017-02842-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of developmental defects in the forebrain resulting from hyperactivated mTOR signaling by integrative analysis of transcriptomic and proteomic data

Abstract: Hyperactivated mTOR signaling in the developing brain has been implicated in multiple forms of pathology including tuberous sclerosis complex (TSC). To date, various phenotypic defects such as cortical lamination irregularity, subependymal nodule formation, dysmorphic astrocyte differentiation and dendritic malformation have been described for patients and animal models. However, downstream networks affected in the developing brain by hyperactivated mTOR signaling have yet to be characterized. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…5a, b). Supporting these findings, we interrogated by GSEA analysis genes known to be targeted by hyperactivated mTOR signaling in TSC1 KO 34 , which revealed an enrichment in DS ( p < 0.001, FDR q < 0.001; Fig. 5c).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…5a, b). Supporting these findings, we interrogated by GSEA analysis genes known to be targeted by hyperactivated mTOR signaling in TSC1 KO 34 , which revealed an enrichment in DS ( p < 0.001, FDR q < 0.001; Fig. 5c).…”
Section: Resultssupporting
confidence: 52%
“…b Phosphorylation levels quantified by densitometry as a ratio of phospho-protein/total protein level ( n ≥ 3). c GSEA of transcriptome changes comparing DS fibroblasts to 2 N fibroblasts, using a list of genes described to be upregulated upon hyperactivated mTOR signaling due to Tsc1 depletion (Shin et al 34 ). As described for Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubers are epileptogenic cortical malformations in TSC. Allana et al showed that both mRNA and protein levels of the DCX protein were higher in TSC nodules than in the control group (43). This result is consistent with our expression of differentially expressed proteins.…”
Section: Discussionsupporting
confidence: 91%
“…To filter out low-quality proteins, selected proteins were detected in at least two samples under each condition. DPPs between T24S and T24R cells were identified using a previously reported statistical test 43 . Briefly, log 2- intensities of each protein from T24R cells were compared to those in T24S cells using the Student's t-test and log 2 -median ratio test.…”
Section: Methodsmentioning
confidence: 99%